2020
DOI: 10.2147/dmso.s231979
|View full text |Cite
|
Sign up to set email alerts
|

<p>Guava Leaf Extract Attenuates Insulin Resistance via the PI3K/Akt Signaling Pathway in a Type 2 Diabetic Mouse Model</p>

Abstract: Background and Objective: Insulin resistance is well known to exhibit essential effects on the progression of diabetes mellitus (DM). Guava leaf was also reported to exhibit antidiabetic effects including decreasing blood glucose. Therefore, this present study aims to explore the role guava leaf extract (GLE) plays in insulin resistance and its mechanism of action via the PI3K/Akt signaling pathway. Methods: KK-Ay mice is a spontaneous genetic type 2 diabetes mouse model induced by feeding a high fat and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…37 Furthermore, in the glucose metabolism pathway, AKT-1 can regulate GSK-3β/GLUT-4 and mTOR/S6K1/IRS-1. 38,39 In this study, DAGL and DAGL·Cr upregulated the relative transcription and protein expression levels of six genes (PI3K, AKT-1, mTOR, GLUT-4, S6K1, and IRS-1) in T2DM mice and downregulated mRNA transcription and protein expression levels of GSK-3β. When PI3K is activated, it produces a second messenger phosphatidylinositol 3,4,5-trisphosphate (PIP3) on the plasma membrane, which binds to the pleckstrin homology domain of protein kinase B (PKB/AKT-1), allowing PDK1 to phosphorylate Ser308 of the AKT-1 protein.…”
Section: Discussionsupporting
confidence: 50%
“…37 Furthermore, in the glucose metabolism pathway, AKT-1 can regulate GSK-3β/GLUT-4 and mTOR/S6K1/IRS-1. 38,39 In this study, DAGL and DAGL·Cr upregulated the relative transcription and protein expression levels of six genes (PI3K, AKT-1, mTOR, GLUT-4, S6K1, and IRS-1) in T2DM mice and downregulated mRNA transcription and protein expression levels of GSK-3β. When PI3K is activated, it produces a second messenger phosphatidylinositol 3,4,5-trisphosphate (PIP3) on the plasma membrane, which binds to the pleckstrin homology domain of protein kinase B (PKB/AKT-1), allowing PDK1 to phosphorylate Ser308 of the AKT-1 protein.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, the PI3K-Akt signaling pathway was significantly enriched on D8 relative to D0. The PI3K-Akt signaling pathway plays a role in cell proliferation, differentiation, apoptosis, glucose metabolism, and lipid metabolism [ 38 ]. The p53 signaling pathway is related to initiating DNA repair, cell cycle arrest, senescence, and apoptosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is characterized by increased adipose tissue mass, which is linked to the onset of insulin resistance and T2DM. Several studies have reported that oral administration of GLE reduced body weight and adipose tissue weight [ 19 20 ]. Adipose tissue mass can be expanded by adipocyte differentiation and subsequent fat accumulation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…During adipocyte differentiation, activation of transcription factors, including peroxisome proliferator activated receptor γ (PPARγ), CCAAT/enhancer-binding protein (C/EBP), and sterol regulatory element-binding protein-1c (SREBP-1c) are required to express lipogenic genes, such as acetyl-CoA carboxylase and fatty acid synthase (FAS) [ 18 ]. Recently, it has been reported that GLE reduced body weight gain and adipose tissue weight in diabetic rodents [ 19 20 ]. Nevertheless, little is known about whether GLE can affect adipogenesis.…”
Section: Introductionmentioning
confidence: 99%